APPROACHES TO DEFINITION OF SOCIAL TOURISM IN THE CONTEXT OF FORMATION OF SOCIAL TOURISM DOCTRINE (INNOVATIVE ECONOMY, 2019)
Felenchak Yu.B. APPROACHES TO DEFINITION OF SOCIAL TOURISM IN THE CONTEXT OF FORMATION OF SOCIAL TOURISM DOCTRINEPurpose. The purpose of the article is to analyze the theoretical approaches to the definition of social tourism that exist in modern science, and to determine the place and importance of social tourism in the context of the development and implementation of the social doctrine of tourism.Methodology of research. Methods of scientific literature analysis (monographic, analytical, abstract and logical) were used to study approaches to understanding the essence of social tourism, features of its organization and its role in the implementation of the social doctrine of tourism.Findings. The article deals with theoretical approaches to the definition of social tourism as an independent direction of tourism research that exist in modern science. Social features of modern tourism development are outlined. The definitions of social tourism developed by domestic and foreign scientists are considered. The social doctrine of tourism is defined as an integral part of the social doctrine of the state. The necessity to develop and implement an effective social doctrine of tourism, taking into account the regional social specificity, is substantiated.Originality. The study of social tourism as an independent tourism direction has been developed. The importance of tourism, its role in the versatile development of personality and the formation of outlook standards of quality and quality of life are emphasized. The place and role of social tourism in the development and implementation of the social doctrine of tourism of the state are outlined.Practical value. The results of the survey can be used in the activities of tourism enterprises of Ukraine and its regions, state authorities and local self-government. Theoretical and methodological generalizations may form the basis for further research in this area.Key words: tourism; social tourism; tourist service; social doctrine; social doctrine of tourism.
Keywords: Key words; tourism; social tourism; tourist service; social doctrine; social doctrine of tourism.